ANALYZING AND EVALUATING THE INFORMATION TECHNOLOGY SYSTEM IN PT. REPEX PERDANA INTERNATIONAL’S LOGISTIC ACTIVITIES - Zulfahmi Azis Rauf (CALYPTRA, 2014)
Innovations are one of the most important jobs that are conducted by almost all organizations, business and firms in order to improve their current operation capabilities. In this research, the chosen company, Repex Perdana International (RPI) the license owner of FedEx International, innovate a new information technology into their system in order to improve their performance in the logistics. The goal of this research is to “analyzing and evaluating the recent implementation of Information Technology (IT) system in RPI, specify in its effectiveness and efficiency”. The purpose of analyzing the IT system is to see what kind of improvement that achieved so far and at the end devise a possible recommendation and suggestion to improve it. As the research undertaken, some conclusions have been made on the basis of research findings which are showing positive results of the investment. However some drawbacks also founded from the system and in the end there will be recommendations to counter these drawbacks, future improvement, as well as future research.